Spletno orodje DancEpos - rešitve za prevencijo poškodb in izboljšanje umetniške uspešnosti v plesu - Pavlović, Monika (Šport (Ljubljana), 2021)
The online tool DancEpos (www.dancepos.com) provides professional, innovative e-solutions to prevent dance injuries and improve artistic performance in dance. The learning content is created specifically for dancers based on scientific evidence. DancEpos‘ e-textbooks include three main sections: (1) General Injury and Athletic Training Basics, (2) Prevention/ Rehabilitation of Common Dance Injuries, and (3) Improving Dance Technique. The educational content of the online tool is delivered in the text form of the e-textbooks while supported by more than 100 images and 40 videos. A brief injury history questionnaire is available for individuals who are unsure of which content to begin with. Based on the results, a report is automatically generated with some recommended exercises based on the individual‘s responses. In addition, (sub)chapters from the e-textbook are suggested where more information is available. The creators of the online tool DancEpos want the content to reach as many dancers of different dance genres as possible and thus contribute to a longer and safer dance career.
Keywords: dance; injuries; mišično-skeletne poškodbe; musculoskeletal injuries; ples; poškodbe; prevention; preventiva